Electricity Generation from Atmospheric Moisture Using a CdS/p‐Si Nanowire Hetero‐Junction Device. Issue 10 (13th September 2022) - Aggarwal, Rinki; Kumar, Avshish; Dhasmana, Hrishikesh; Verma, Abhishek; Jain, Vinod K.; Sengupta, Sucheta
Abstract: One‐dimensional heterojunction devices are gaining attention because of improved carrier collection which results in improving the overall efficiency of a device. Herein, we report the synthesis of a CdS/p‐Si nanowire (NW) hetero‐junction device by wet‐chemical methods and their potential application for electricity generation from atmospheric moisture. A single CdS/p‐Si NWs hetero‐junction based moisture enabled electricity generator (MEG) device exhibits a saturated maximum output voltage in the range of 250–300 mV and a saturation current of ∼0.2 μA in presence of humid conditions. This primitive module acts as a promising candidate for future energy generation devices constituting of individual units connected either through simple series or parallel connection to scale up high electrical power. Abstract : We report the fabrication of a CdS/p‐Si nanowire hetero‐junction by a cost‐effective, facile chemical bath deposition (CBD) technique and their consequent application for electricity generation from atmospheric moisture. An optimum output voltage in the range of ∼250–300 mV and a maximum current of 0.2 μA was observed for a single primitive device.